ATHEISM ITS REALITY AND HOW TO CONFRONT IT - Dr. Adel Muhammad Abdul Qadir Ali, Sultan Abdul Halim Muadzam Shah (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Praise be to God, and May blessings and peace be upon the Messenger of God and his family, companions and those who follow him. Afterwards: The emergence of atheism in the beginning was not a separate phenomenon that came on its own, but was a reaction to the situation of European societies in the middle Ages, where popes and priests used to dominate people on the pretext that they derive their authority directly from God. The matter continued until "Darwin" appeared with his theory of the evolution and emergence of species according to the mechanism of natural selection. At that time, the beliefs of atheism began to take root among some, and voices appeared calling for the death of God, as the famous German philosopher Nietzsche said. However, with the beginning of the twentieth century and the escalation of the movement of discoveries and scientific research, man began to submit to the clear fact that he is still only at the beginning. Whenever scientists discover something new, it appears to them that they are still ahead of them. Since that time and until now, people, especially scientists, have been divided between those who are becoming more and more envious of science, and that there is no longer a need for a god for this universe, and others who have called for intelligent or great design, and that this universe was created from a miraculous force capable of everything.